Withdrawal from Correspondent Banking : Where, Why, and What to Do About It - World Bank Group (World Bank, Washington, DC, 2015)
Correspondent banking services are essential to enabling companies and individuals to transact internationally and make cross-border payments. Recently there have been indications that certain large international banks have started terminating or severely limiting their correspondent banking relationships with smaller local and regional banks from jurisdictions around the world. To find out whether this is indeed happening, the World Bank, with support from the Financial Stability Board (FSB) and the Committee on Payments and Market Infrastructures (CPMI), surveyed banking authorities and banks worldwide to examine the extent of withdrawal from correspondent banking, its drivers, and its implications for financial exclusion/inclusion. In total, 110 banking authorities, 20 large banks, and 170 smaller local and regional banks participated in this exercise. This document includes finding of the survey, conclusions, and recommendations.